PENGARUH MODEL PROBING PROMPTING TERHADAP PENINGKATAN KEMAMPUAN BERPIKIR KRITIS MATEMATIS PESERTA DIDIK SMP - Dwi Sulistiana (Universitas Islam Nusantara, 2020)
The less mathematical critical ability of learners was the one of the problem that observed in this study.Probing Prompting model was the one of the alternative learning that can be applied to improve the mathematical critical ability of learners. The purpose of this study was to know the influence of increased the mathematical critical ability by using Probing Prompting learning model, and students' perceptions of assessment in mathematical learning. Non-equivalent control group design was used in this quarsi-experimental study. The research conducted in one of the Junior High Schools in Bandung Districts. The population of the study were all students in a second grade, the sample of this study werestudents of VIII E as experimental class and VIII B as the control class. Experimental class was applied the Probing Prompting learning model and the control class was applied the Discovery Learning model. Mathematical critical ability test, questionnaire, and observation sheet were the instruments of this study. The result of the study were qualitative and quantitative data. Depend on the analysis of the result, it can be concluded that Probing Prompting model has an influence in the learning process on improving mathematical critical abilityand the students’ perceptions of assessment in mathematical learning model was positive.